An application of lingo software to solve dynamic programming problem in the field of environmental protection - Baoyou Liu; Nanxi Jin (2015 IEEE Advanced Information Technology, Electronic and Automation Control Conference (IAEAC), 2015)
Based on the practical problems in the field of environmental protection, this article analyzes and optimizes the sales and storage problems and resource allocation problems of two typical cases by the means of building the mathematical model of the dynamic programming and using lingo11 to solve it. The results show that the lingo11 can be used as a effective tool to solve the optimization problems in the field of environmental protection for its high computing speed and accuracy of the method. Also it is suitable for used in similar problems.